Emergency Pancreatoduodenectomy with Preservation of Gastroduodenal Artery for Massive Gastrointestinal Bleeding due to Duodenal Metastasis by Clear Cell Renal Cell Carcinoma in a Patient with Celiac Artery Stenosis - Kyriakos Neofytou; Alexandros Giakoustidis; Martin Gore; Satvinder Mudan (Case Reports in Surgery)
Duodenal metastasis from renal cell carcinoma is rare, and even rarer is a massive gastrointestinal bleeding from such tumours. Coeliac occlusive disease, although rarely symptomatic, can lead to ischaemic changes with anastomotic dehiscence and leaks when a patient undergoes pancreatoduodenectomy. A 41-year-old man with known metastasis to the adrenal glands and the second part of the duodenum close to the ampulla of Vater from clear cell renal cell carcinoma was admitted to our department due to massive gastrointestinal bleeding from the duodenal metastasis. Endoscopic control of the bleed was not possible, while the bleeding vessel embolization was able to control the haemorrhage only temporarily. An angiography during the embolization demonstrated the presence of stenosis of the coeliac artery and also hypertrophic inferior pancreaticoduodenal arteries supplying the proper hepatic artery via the gastroduodenal artery (GDA). The patient underwent emergency pancreatoduodenectomy with preservation of the gastroduodenal artery. The patient had an uneventful recovery and did not experience further bleeding. Also the blood flow to the liver was compromised as shown by the normal liver function tests (LFTs) postoperatively. To the best of our knowledge, this is the first report of a preservation of the GDA during an emergency pancreatoduodenectomy.